Can Selenium Promote the Hormesis Effect on Germination and Quality of Peanut (Arachis hypogaea L.) Seeds? - Cunha, Matheus Luís Oliveira [UNESP]; Alves de Oliveira, Lara Caroline [UNESP]; Tacca, Júlio Guilherme [UNESP]; Rodrigues dos Reis, André [UNESP] (Springer Nature, 2023)
In this study we hypothesize that Se increase nitrogen (N) compounds and sugars in the endosperm boosting seed germination. This study aimed to verify the influence of seed peanut fertilization with selenium (Se) on seed quality and germination. The treatments consisted of five doses of Se (0, 7.5, 15, 30 and 45 μg kg−1) applied in the mother plants via soil. In the grains, the concentration of amino acids, sugars, storage proteins and the content of macro and micro nutrients were evaluated. In the seedlings, the concentration of N-compounds, germination, length and fresh weight of the shoot and root were evaluated. Se at a dose of 15 µg kg−1 increases the concentration of amino acids and sugars in the grains and promotes greater germination, shoot and root length and nitrogen compounds in peanut seedlings. Se increases the concentration of prolamine and globulin in all doses. In addition, fertilization of plants with Se increased the nutritional content of Fe, Na and Se, which might be a good alternative to increase daily intake of micronutrients by the population lacking in human body. This study presents new insights into the effects of Se on germination and development of peanut seedlings that may be important for increasing plant population in commercial crops. Our results are important for peanut consumers due to the increase in the nutritional value of the seeds and for peanut producers due to the increase in germination and physiological quality of seeds.
Keywords: Amino acids; Nitrate; Root lenght; Seedlings; Shoot lenght; Total sugar